Promotion of High-Quality and Respectful Care of Newborns. Issue 4 (July 2021) - Callister, Lynn Clark
Abstract : Mothers and babies deserve high-quality, respectful maternity and newborn care. Our global health expert, Dr. Callister, explains some of the global initiatives from around the world to make sure newborns get evidence-based care at birth and what nurses can do to support those activities.